2011
DOI: 10.1159/000322862
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Cardiovascular Disease Predicts Chronic Kidney Disease Awareness in the Kidney Early Evaluation Program

Abstract: Aims: Lack of chronic kidney disease (CKD) awareness is common. Recent data suggest that the presence of concurrent diabetes may heighten CKD awareness, but current data have not supported the hypothesis that healthcare delivery or insurance status improves awareness in the diabetic population. Diabetes is associated with high cardiovascular disease (CVD) morbidity, especially in patients with CKD. We hypothesized that a highly prevalent co-morbid condition such as CVD in patients with diabetes would predict C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…6 However, hypertension and diabetes have a longer history of understanding by primary care healthcare providers and public health awareness campaigning. Previous studies have reported that more men than women were aware of their diagnosis of CKD, 6,7 and the present study has found similarly that 64% of those who were not aware of their diagnosis were female. When analysing variables associated with awareness, risk factors for CKD and cardiovascular disease surprisingly did not show a significant association in the present study cohort.…”
Section: Comparison With Existing Literaturesupporting
confidence: 73%
See 1 more Smart Citation
“…6 However, hypertension and diabetes have a longer history of understanding by primary care healthcare providers and public health awareness campaigning. Previous studies have reported that more men than women were aware of their diagnosis of CKD, 6,7 and the present study has found similarly that 64% of those who were not aware of their diagnosis were female. When analysing variables associated with awareness, risk factors for CKD and cardiovascular disease surprisingly did not show a significant association in the present study cohort.…”
Section: Comparison With Existing Literaturesupporting
confidence: 73%
“…Nevertheless, studies from the US suggest that patient awareness of CKD is poor. 6,7 A second aim of this study was to assess awareness of the diagnosis in the study cohort of patients with CKD stage 3.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of CKD, normal serum levels of phosphorus and calcium are maintained through integrative actions of two hormones: parathyroid hormone (PTH) and 1,25-dihydroxyvitamin D 3 (calcitriol), the principal metabolite that activates the vitamin D receptor [20][21][22][23][24][25][26][27][28][29] . There is also increasing evidence to support the existence of various factors (historically known as phosphatonins) that directly control the renal excretion of phosphorus, and elucidation of their precise role in the regulation of phosphorus metabolism is an area of active research [20,29,30] .…”
Section: Normal Phosphate Homeostasis and Alterations In Ckdmentioning
confidence: 99%
“…The prevalence of CKD is approaching epidemic proportions worldwide [1,2] . More than 26 million Americans, or 13% of the total population, have CKD [3] . Most patients with CKD die prematurely, not from kidney failure, but from early onset of common diseases, such as cardiovascular disease (CVD), cancer, and infection [3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation